Effects of yoga-based interventions on cognitive function in healthy older adults: A systematic review of randomized controlled trials - Sara Hoy; Josefine Östh; Michaela Pascoe; Aaron Kandola; Mats Hallgren (Elsevier, 2021)
Background: The world's elderly population is growing. Physical activity has positive effects on health and cognition, but is decreasing among the elderly. Interest in yoga-based exercises has increased in this population, especially as an intervention targeting balance, flexibility, strength, and well-being. Recent interest has arisen regarding yoga's potential benefits for cognition. Objective: To systematically review evidence from randomized controlled trials (RCTs) examining the effects of yoga-based interventions on cognitive functioning in healthy adults aged ≥60. A secondary aim was to describe intervention characteristics and, where possible, the extent to which these influenced study outcomes. Method: The review was conducted in accordance with PRISMA guidelines. Searches were performed from inception to June 2020 using the following electronic databases: (1) PubMed (NLM); (2) Embase (Elsevier); (3) Cochrane Central (Wiley); (4) PsycINFO (EBSCOhost); and (5) Cinahl (EbscoHost). Inclusion criteria: RCTs of yoga-based interventions assessing cognition in healthy adults ≥60 years. Risk of bias was assessed using the revised Cochrane risk of bias tool. Results: A total of 1466 records were initially identified; six studies (5 unique trials) were included in the review. Four of the six articles reported significant positive effects of yoga-based interventions on cognition, including gross memory functioning and executive functions. Intervention characteristics and assessment methods varied between studies, with a high overall risk of bias in all studies. Conclusion: Yoga-based interventions are associated with improvements in cognition in healthy older adults. Adequately powered RCTs with robust study designs and long-term follow-ups are required. Future studies should explicitly report the intervention characteristics associated with changes in cognitive function.